Pengaruh Transfer Pricing, Kompensasi Rugi Fiskal, Leverage, dan Kualitas Audit Terhadap Praktik Penghindaran Pajak pada Perusahaan BUMN yang telah Go Publik untuk Periode 2017-2020 - Meiti Angel; Friska Darnawaty; Lidya Liona (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to examine the effect of transfer pricing, fiscal loss compensation, leverage, and audit quality on tax avoidance in BUMN companies listed on the Indonesia Stock Exchange in 2017-2020 period. The existence of different interests between the taxpayer and the government tends to make the taxpayer seek to reduce the amount of tax payment both legally and illegally. This research used a method with a quantitative descriptive approach. The population in this study were BUMN companies listed in Indonesia Stock Exchange (IDX) during the period 2017 to 2020 with a total of 20 companies and the sampling technique used purposive sampling and obtained 13 companies in BUMN companies. Data analysis used multiple linear regression analysis, classical assumption test, the coefficient of determination test, F test and t test. The results of the study show that partially fiscal loss compensation, leverage and audit quality have significant effect on tax avoidance but transfer pricing has no effect on tax avoidance. Variable transfer pricing, fiscal loss compensation, leverage and audit quality simultaneously have a significant effect on tax avoidance in BUMN companies listed on Indonesia Stock Exchange in 2017-2020.